Analisis Beberapa Faktor Yang Mempengaruhi Pendapatan Petani Padi Di Desa Cau Belayu Kecamatan Marga Kabupaten Tabanan - Guna, I Nyoman Ariana; Sarjana, I Wayan Mula; Rastana, I Dewa Gede (Universitas Tabanan, 2025)
Cau Belayu Village, as one of 16 villages in Marga District, Tabanan Regency, Bali Province, from 2018 to 2022 experienced a decline in rice production, resulting in a decrease in income which was influenced by many factors, including weather, season, pests, network factors. irrigation, land area, capital, labor and other factors. The aim of this research is to determine the influence of land area, capital and number of workers on the income of rice farmers in Cau Belayu village, Marga subdistrict, Tabanan district. The location of this research was carried out in Cau Belayu Village, Marga District, Tabanan Regency using primary data sourced from rice farmers and secondary data sourced from Pekaseh Subak Cau Belayu, perbekel offices and other related parties, then processed and analyzed using regression analysis multiple linear. Based on the SPSS calculation results, the following results were obtained: (1) land area has a partially positive and significant effect on the income of rice farmers in Cau Belayu Village, Marga Subdistrict, Tabanan Regency, (2) capital has a partially positive and significant effect on the income of rice farmers in Cau Belayu Village, Subdistrict Marga, Tabanan Regency, (3) the number of workers has a negative but not partially significant effect on farmers' income in Cau Belayu Village, Marga District, Tabanan Regency, (4) land area, capital and number of workers have a simultaneously significant effect on the income of rice farmers in the village Cau Belayu, Marga District, Tabanan Regency. The results of the analysis of the coefficient of multiple determination (R2) explain that the variation in income of rice farmers in Cau Belayu Village, Marga District, Tabanan Regency is 89.40 percent influenced by land area, capital and number of workers and the remaining 10.60 percent is influenced by variables. other variables outside the model were not included in this study.